Genetic structure and current distribution of Liriomyza huidobrensis, L. sativae and L. trifolii (Diptera: Agromyzidae) on vegetable crops in Bali, Indonesia - I WAYAN EKA KARYA UTAMA; I WAYAN SUPARTHA; KETUT AYU YULIADHI; I PUTU SUDIARTA; I KADEK WISMA YUDHA; SAHABUDDIN SALEH; SRI WAHYUNI; PUTU ANGGA WIRADANA (Society for Indonesian Biodiversity, 2024)
Abstract. Utama IWEK, Supartha IW, Yuliadhi KA, Sudiarta IP, Yudha IKW, Saleh S, Wahyuni S, Wiradana PA. 2024. Genetic structure and current distribution of Liriomyza huidobrensis, L. sativae and L. trifolii (Diptera: Agromyzidae) on vegetable crops in Bali, Indonesia. Biodiversitas 25: 2104-2114. Liriomyza spp. (Diptera: Agromizidae) is a polyphagous pest that attacks various types of vegetable and ornamental plants throughout the world. The most damaging species are Liriomyza huidobrensis (Blanchard), Liriomyza sativae (Blanchard), and Liriomyza trifolii (Burgess). There have been no reports regarding mapping of population distribution and population genetics of Liriomyza in the Bali region using the Cytochrome C Oxidase Subunit I (COI) approach. This research aims to map the population and genetic structure of L. huidobrensis, L. sativae and L. trifolii on vegetable plants in Bali. This research uses a purposive sampling method which represents vegetable plantings in each district and city in Bali Province. Identification of the Liriomyza spp. gene structure using the COI approach using LCO and HCO primers. The results of the research found that the spatial distribution of invasive leafminer fly species, namely L. sativae and L. trifolii, was evenly distributed throughout the city districts in Bali. The distribution pattern of L. trifolii is uniform with an S2/X value <1, while L. huidobrensis is found in the highland areas with a clustered distribution pattern with an S2/. The genetic distance between the three Liriomyza species found in vegetable plants in Bali is much longer. This means that the three Liriomyza species show very high levels of genetic differentiation in mitochondrial and nuclear genes, and differentiation between species in nuclear genes. This genetic variation can influence the ability of insects to quickly adapt to new environments and contribute to population dynamics and dispersal capacity.